2021
DOI: 10.3389/fneur.2021.645822
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for LASER: A Randomized Evaluation and an Associated Registry of Early Anticoagulation With Edoxaban After Ischemic Stroke in Patients With Atrial Fibrillation

Abstract: Background: The optimal timing of anticoagulation after stroke in patients with atrial fibrillation (AF) is unknown.Aim and Hypothesis: Our primary aim is to demonstrate the safety of edoxaban initiation within 5 days of AF related stroke. Our secondary aim is to determine predictors of hemorrhagic transformation (HT) after AF related stroke. We hypothesize that the rate of radiological HT will not be increased in patients starting edoxaban within 5 days of AF related stroke, relative to those in whom initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Randomized trials currently assessing safety/efficacy of earlier versus later DOAC include ELAN (NCT03148457), START (NCT03021928), and OPTIMAS (NCT03759938). 26,[34][35][36] Even after pooling, our studies contain far too few patients to determine the effect of early DOAC initiation on the clinically relevant endpoints of symptomatic ischemic stroke, intracranial hemorrhage, and death. Based on low event rates, a sample size of approximately 3000 patients is required to adequately address this question, and trials like OPTIMAS have been designed accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials currently assessing safety/efficacy of earlier versus later DOAC include ELAN (NCT03148457), START (NCT03021928), and OPTIMAS (NCT03759938). 26,[34][35][36] Even after pooling, our studies contain far too few patients to determine the effect of early DOAC initiation on the clinically relevant endpoints of symptomatic ischemic stroke, intracranial hemorrhage, and death. Based on low event rates, a sample size of approximately 3000 patients is required to adequately address this question, and trials like OPTIMAS have been designed accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies suggesting that LAA thrombus results from atrial cardiopathy: dilatation of the atrium, endothelial dysfunction, and blood stasis are all factors that contribute to clot formation, as shown by Tsao et al 8 Our previous work also suggested the benefit of early diagnosis of LAA thrombus in the initiation of anticoagulation therapy without additional risk of bleeding. 6 Randomized studies comparing early versus late anticoagulation in patients with AF related stroke are ongoing and will provide safety as well as efficacy robust data on these strategies (ELAN 22 and LASER 23 trials)…”
Section: Discussionmentioning
confidence: 99%
“…The question of optimal timing to start DOAC will remain unanswered until randomized trials of early versus delayed DOAC are completed (Table 2). 122125 Ongoing trials include LASER (Lixiana Acute Stroke Evaluation Registry, NCT03494530), TIMING (Timing of Oral Anticoagulant Therapy in Acute Ischemic Stroke With Atrial Fibrillation: a Prospective Multicenter Registry-based Non-inferiority Randomized Controlled Clinical Trial, NCT02961348), ELAN (Early Versus Late Initiation of Direct Oral Anticoagulants in Post-ischaemic Stroke Patients With Atrial fibrillation, NCT03148457), START (Optimal Delay Time to Initiate Anticoagulation After Ischemic Stroke in Atrial Fibrillation, NCT03021928) trials, and OPTIMAS (OPtimal TIming of Anticoagulation After Acute Ischemic Stroke, NCT03759938).…”
Section: Future Directionsmentioning
confidence: 99%
“…The observed current practice of delaying DOAC initiation in patients with larger infarcts is relevant to the ongoing RCTs, where randomization is either stratified by infarct volume/size 123 ELAN, NCT03148457 and/or includes arms with relatively broad initiation time windows of several days, extending up to 14 days after symptom onset. 122,124 OPTIMAS, NCT03759938 This form of stratification by infarct volume or by having broad initiation time windows where the decision to time the treatment at the treating physician’s discretion, even in the context of randomization, may play a role in introducing a bias. It may also limit the understanding of whether the timing of DOAC initiation should be adjusted based on infarct size and/or clinical severity of the index event to reduce the risk of HT.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation